Book review: Free Loaves on Fridays: The Care System As Told By People Who Actually Get It. By Rebekah Pierre, Publisher: Unbound, ISBN:978-1-80018-300-1 - Jim Goddard (Scottish Journal of Residential Child Care)
One sees content warnings everywhere. This book is no exception. Such a warning is probably more necessary for those who weren’t brought up in the UK child care system than for those of us who were. The latter will be familiar with experiences which the former might find shocking. Indeed, reading of the inner lives of those raised in care can be startling. Their frequent invisibility in their own homes and in the wider world is often only altered when their behaviour raises problems for adults. One calls to mind George Eliot’s words in Middlemarch: ‘If we had a keen vision and feeling of all ordinary human life, it would be like hearing the grass grow and the squirrel’s heartbeat, and we should die of that roar which lies on the other side of silence’ (Eliot, 1999, pp. 216-217). Hence the content warning.